Potential Value of Serum Lipid in the Identication of Postoperative Delirium Undergoing Knee/Hip Arthroplasty: The Perioperative Neurocognitive Disorder and Biomarker Lifestyle Study - Lin, Yanan; Peng, Xiaoyan; Lin, Xu; Deng, Xiyuan; Liu, Fanghao; Tao, He; Dong, Rui; Wang, Bin; Bi, Yanlin (Frontiers in Psychiatry, 2022)
Objective: We aimed to investigate the relationship between preoperative lipid level and postoperative delirium (POD) and explore whether lipid's effect on POD is mediated by POD core protein.Methods: A total of 635 patients who were planned to undergo knee/hip arthroplasty under combined spinal-epidural anesthesia were selected. The Mini-Mental State Examination was completed one day before the operation. 5ml elbow venous blood was taken from the patients before anesthesia, and serum levels of total cholesterol (TG), triglyceride (TC), low-density lipoprotein (LDL-C), and high-density lipoprotein (HDL-C) were detected. Cerebrospinal fluid (CSF) was extracted after successful spinal-epidural combined puncture, and amyloid beta40 (Aβ40), amyloid beta42 (Aβ42), t-Tau, and phosphorylated Tau (p-Tau) in the CSF were measured by enzyme-linked immunosorbent assays (ELISA). After the operation, the occurrence and severity of POD were assessed using the Confusion Assessment Method and the Memorial Delirium Assessment Scale (MDAS), respectively. Patients were categorized into POD group and NPOD group. Logistic regression was used to analyse the relationship between POD and TG, TC, HDL-C, and LDL-C, and the mediating effect was used to analyse the role of POD core proteins (Aβ42 and t-Tau) in the relationship between lipid and MDAS..Results: A total of 562 patients were finally enrolled in this study, and 66 patients developed POD, with an incidence of 11.7%. Logistic regression analysis showed that high concentration of TC (OR=3.148,95%CI 1.858~5.333 ), TG (OR=2.483,95%CI 1.573~3.918), and LDL-C (OR=2.469,95%CI 1.310~4.656) in serum were risk factors for POD. A high concentration of HDL-C (OR=0.258,95%CI 0.112~0.594) was a protective factor for POD. ROC curves show that HDL-C had the highest sensitivity and specificity in predicting POD. The mediating analysis showed that Aβ42 and t-Tau could partially mediate the relationship between lipid and POD. The results were barely changed in the sensitivity analysis, and the sensitivity analysis has shown that the results were stable.Conclusion:The increase of serum TG, TC, and LDL-C concentration is a risk factor for POD development, while high HDL-C concentration is a protective factor for POD, and the occurrence of POD is caused by hyperlipidemia may be caused by POD core protein (Aβ42 and t-Tau).